In Search of a DisSchool: Deficit and Inclusion in Danish Schools - Ida Andrea Nilsson (Scandinavian Journal of Disability Research)
This paper takes a Critical Disability Studies (CDS) approach to examine how deficit-based and inclusive practices appear in Danish schools. Although inclusive education is a guiding star in policy, research shows that its transformative aims are often overridden by deficiency-informed approaches. Drawing on interviews with school staff and ethnographic fieldwork in a Danish primary school, the paper examines how dis/ability disrupts ableist educational norms, instigating change. The analysis operationalises the concept ‘DisSchool’ to trace how schools respond to such disruptions—either by reinforcing existing structures or by reorganising practice in more inclusive directions. The paper offers a practice-near framework for distinguishing between inclusive and deficiency-based approaches in everyday pedagogic interactions, arguing that many inclusive efforts are limited by entrenched deficiency perspectives. By using CDS to illuminate how inclusive potentials emerge and are constrained in everyday practice, the paper contributes to bridging the gap between theory and practice in inclusive education.